Peran Storyline pada Representasi Identitas Nasional di Museum Nasional Indoensia Baru - Liliek Adelina Suhardjono; Budi Sriherlambang; Laura Christina Luzar (Universitas Trisakti, 2018)
AbstractNational Identity Representation of the New National Museum of Indonesia. The Collection of the National Museum of Indonesia is a manifest of national identity. The National Museum should represent various elements that define an identity of a nation. At the same time we also need to critically assess the role of the National Museumin the construction of nation identity. Since the beginning of its founding, Indonesia is a nation with diverse components. However in recent times there have been many instances where people seem to have forgotten the importance of these diversities. At the moment the National Museum of Indonesia is undergoing a major restoration with the strategy to incorporate storyline as a path to present its collections. This researchaims to assess the representation of national identity within this new approach. By incorporating observation on the National Museum of Indonesia and Linggarjati Museum as comparative studies as a methodology, continued with interviews, analysis and synthesis. The final result of this research will give a recommendation that hopefullywill give benefit the National Museum of Indonesia. AbstrakPeran Storyline pada Representasi Identitas Nasional di Museum NasionalIndonesia Baru. Koleksi Museum Nasional Indonesia merupakan manifestasi dari sebuah identitas nasional. Museum Nasional hendaknya merepresentasikan berbagai elemen yang menentukan ide ntitas suatu negara. Di lain pihak kita hendaknya juga terus bertanya, peran apakah yang dimainkan oleh Museum Nasional atas konstruksi identitasbangsa? Bangsa Indonesia adalah bangsa yang berbhinneka. Namun akhir-akhir ini, berbagai peristiwa yang mencederai kebangsaan seakan menjadi pertanda bahwa banyak di antara masyarakat kita yang mulai melupakan pentingnya keberagaman. Saat ini, Museum Nasional hendak berbenah diri, melebarkan sayap dan membangun tata visual baru dengan berdasar pada storyline. Penelitian ini bertujuan untuk mengkajirepresentasi identitas nasional pada Museum Nasional Indonesia yang baru. Penelitian ini menggunakan metodologi observasi pada Museum Nasional Indonesia dan Museum Linggarjati sebagai pembanding, dilanjutkan dengan tahapan wawancara, analisis dan sintesa. Hasil akhir dari penelitian berbentuk kajian ini berupa rekomendasi yang dapatdigunakan sebagai rujukan oleh pihak Museum Nasional Indonesia.